(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Infection of the urinary tract is the second commonest site after respiratory tract infection. It is more frequent in women than men. Almost 50% women suffer UTI. In our classical texts, urinary tract infection is described as Mutrakruchcha. A great Acharya Charak has mentioned it in Chikitsa sthana, Trimarmiya adhyay, its 8 types and Basti as a Marma. For the treatment of all types of Mutrakruchcha, Gokshur is mentioned. Gokshur is diuretic, aphrodisiac, tonic and rejuvenating herb with the ability to build lean muscle and strength. Gokshur possess Madhur rasa, Madhur vipaka and sheet Virya which causes diuresis by increasing Kleda in the body. So in this study 30 patients complaining of urinary tract infection were taken. 50 ml of Gokshur decoction, twice a day was given orally for 30 days. Weekly assessment was done on the basis of sign and symptoms like Mutra daha (burning micturition), Sashula mutrapravruti (painful micturition), Bastishul (suprapubic pain), Mutrapravruti (frequency of micturition), Jwaraprachiti (fever with chills), Sarakta mutrapravruti (haematuria), Sapuya mutrapravruti (pyuria). Objective improvement was done on the basis of reduction in pus cells in urine and serum creatinine at initial and after 30 days. Subjective improvement was shown in percentage it was 67.71%. The observations were found to be significant. Paired t test was found to be highly significant at 1 % level of significance i. e. p < 0. 01.